Accounting Information Systems, Financial Report Quality and Internal Control Systems as Moderating Variables - Akwila Josepina; I Ketut Sujana (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
This study aims to determine the effect of Accounting Information Systems on the Quality of Financial Statements moderated by the Internal Control System. The population in this study were all SKPDs in the Denpasar City Government. The sample determination was carried out using the Purposive sampling method. This study uses primary. Respondents in this study totaled 83 respondents. The data analysis method used is Moderated Regression Analysis. The results showed that the Accounting Information System had a positive effect on the Quality of Financial Statements but the Internal Control System was unable to moderate the effect of the Accounting Information System on the Quality of Financial Statements.